Quantum Dots- Tiny Semiconductor Nanodots - Tabassum Khan Nida; Jibran Khan Muhammad (Journal of Advances in Nanotechnology, 2019)
Quantum dots can be defined as semiconductor nanostructures which are artificial in nature and ranges from 2-10 nm in size. These tiny nanocrystals become excited under illumination and emits colors of different wavelength. Quantum dots possess unique properties determined by their structure (hollow or solid), size, shape and composition. Fabrication of Quantum dots is achieved by several methods such as electron beam lithography, epitaxy or by means of colloidal synthesis.
Keywords: DNA assays